Meningkatkan Kemampuan Mengenal Huruf Vokal Melalui Video Learning di TK Roda Junior Tomohon - Putri, Ni Luh; Lumi, Jessica Christiefa (Peneliti.net, 2023)
Research at Roda Junior Kindergarten Tomohon aims to improve the ability to recognize vowels through video learning using two cycle PTK. The research subjects were 15 children consisting of 10 boys and 5 girls. This is motivated by the low ability of children to recognize vowel letters. Data collection techniques through observation, tests, documentation, reflection. Data analysis technique through descriptive analysis, the use of video learning to increase the ability to recognize vowels in cycle I, namely 60% MB and increasing in the cycle reaching 95.5% BSB, the difference in improvement between cycle I and cycle II is 33.3%. Thus, it can be concluded that the use of video learning can improve the ability to recognize vowels in Roda Junior Tomohon Kindergarten for group B children aged 5-6 years.